Selective Catalytic Hydrogenation of Vegetable Oils on Lindlar Catalyst - Laverdura, Umberto Pasqual (ACS Omega, 2020)
[Image: see text] Selective hydrogenation of vegetable oils is a significant step in the synthesis of several precursors for the preparation of bioplastics and biodiesel. In this work, a commercial Lindlar catalyst (palladium on calcium carbonate; poisoned with lead) was used as an efficient catalyst in the selective partial hydrogenation of canola and sunflower oils. Different operating conditions (pressure, temperature, and catalyst amount) were tested, and results were achieved by gas chromatography analysis of methyl esters obtained by the transesterification of the triglycerides. The optimized reaction conditions (0.4 MPa, 180 °C, 4 mg(catalyst)/mL(oil)) were determined for the hydrogenation of linoleic acid (C18:2) and linolenic acid (C18:3) with 84.6 and 90.1% of conversion, respectively, into 88.4% relative percentage of oleic acid (C18:1) with low formation of C18:0 (stearic), below 10%, with stability of the catalyst during several cycles with maximum C18:1 relative percentage ranging between 86.6 and 80.7%.